2010
DOI: 10.1039/c003584j
|View full text |Cite
|
Sign up to set email alerts
|

The use of scanning contactless conductivity detection for the characterisation of stationary phases in micro-fluidic chips

Abstract: The use of scanning capacitively coupled contactless conductivity detection for the evaluation of the structural homogeneity and density of both packed and monolithic stationary phases in microfluidic chips is presented here for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…C 4 D continues to be used as a diagnostic tool in the characterization of monolithic chromatographic columns for IC and HPLC . The homogeneity of the stationary phase in a microfluidic chromatography chip has also been determined . A recent review article by Connolly et al gives a comprehensive overview of the applications of scanning C 4 D in the characterization of various capillary columns.…”
Section: C4d In Other Flow‐through Methodsmentioning
confidence: 99%
“…C 4 D continues to be used as a diagnostic tool in the characterization of monolithic chromatographic columns for IC and HPLC . The homogeneity of the stationary phase in a microfluidic chromatography chip has also been determined . A recent review article by Connolly et al gives a comprehensive overview of the applications of scanning C 4 D in the characterization of various capillary columns.…”
Section: C4d In Other Flow‐through Methodsmentioning
confidence: 99%
“…Walsh et al reported the use of scanning C 4 D (sC 4 D) for the evaluation of the structural homogeneity and density of both packed and monolithic stationary phases in microfluidic chips. 84 The chip was placed on top of the substrate containing the copper electrodes and, by sliding the chip through the microchannel, the packed columns were sequentially scanned along their whole length, from the beginning to the end as illustrated in Fig. 7(A).…”
Section: Other Applicationsmentioning
confidence: 99%
“…In the recent years, progresses in micro and nanofabrication techniques enabled a better control of the positioning of microscale electrodes and especially of the thickness of the insulating layer that can be deposited on them. These technical innovations in microelectrode network design and fabrication allowed new insights in contactless application fields such as scanning conductivity, [1], [2] dielectrophoresis actuation, [3], [4], [5], [6] microfluidic pumps, [7], [8] droplets generator, [9] particle sorting [10], [11] and biosensors. [12], [13], [14], [15], [16], [17] Furthermore, an important research topic in the last decade is the development of flexible polymer microdevices for bioanalytical applications integrating electrodes for biodetection.…”
Section: Introductionmentioning
confidence: 99%